Intra- and inter-rater reliability of ocular phoria tests: Reliability of eye strength tests - G. Paula, Vanessa Cristina; D. A. Tsunoda , Tiago; Fernandes Pires, Paulo; Antonio C. Andraus , Rodrigo; B. B. Alves, Odivan; Alves de Oliveira, Giani; A. Teixeira, Bárbara; Luis S. Luchesi, Guilherme; M. Bento , Felipe; Carlos dos Santos , Denis; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Ocular fusion is responsible for maintaining adequate binocular alignment in relation to the distance from the fixation point to project the image onto the retina of both eyes and obtain a single fused image. Ocular phorias occur when there is a misalignment visualized when breaking binocularity, and are classified according to the direction of the deviation in the literature lacks information on the tests used to evaluate ocular phoria. Objective: This study has as objective to verify the intra- and inter-rater reliability of the ocular phoria test. Methods: Study cross-sectional observational type case-control. They were recruited voluntarily, 123 volunteers from both sexes from 18 to 49 years old. It was the coveruncover test was applied for evaluation qualitative alignment of the axes visuals. The test was accomplished by 3 reviewers distinct in 2 days. The linear weighted Cohen’s Kappa was used to determine reliability and agreement inter-evaluators he was calculated between three pairs of therapists. Results: The reliability of the right ocular phoria test at 40cm showed agreement acceptable in all the tests, already on the left at 40cm the agreement no he was acceptable inter-evaluators in the first evaluation and intra- evaluators, and was acceptable in the second assessment inter-rater reliability. The intra- and inter-rater reliability of the ocular phoria test at 20 cm did not he was acceptable. Conclusion: The ocular phoria test in this moment, due to the low quality of evidence, cannot be recommended for evaluation of ocular phoria.